2024
DOI: 10.1021/acs.cgd.4c00037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ligands on Quantum Tunneling of Magnetization for Dysprosium C4v Single-Molecule Magnets with Theoretical Insights

Jiyuan Du,
Botan Li,
Jiale Tian
et al.

Abstract: Two mononuclear Dy III -based compounds formulated as [Dy(L-pyra) HL-pyri = N 3 -(2-pyridoyl)-3-pyridinecarboxamidrazone) have been synthesized by modifying the ligands with different functional groups. In two compounds, Dy III centers all feature on N 4 O 5 in a spherical capped square-antiprismatic geometry with C 4v configuration. The magnetic studies showed that 1 and 2 display single-molecule magnet (SMM) behavior under a zero dc field with energy barriers of 175.44 and 322.96 K, respectively. Such an ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…Using the obtained parameters, we fitted both the Orbach and Raman processes (τ –1 = CT n + τ 0 –1 exp(− U eff / kT )) over the entire temperature region (10.0–30.0 K). Thus, the excellent fit to the overall relaxation was obtained, and parameters were obtained: U eff = 197.44 K (137.22 cm –1 ), τ 0 = 3.03 × 10 –7 s, C = 8.69 × 10 –5 s –1 ·K – n , n = 5.07, R 2 = 0.999, where the n value and τ 0 were consistent with normal value (1 < n < 6 and 10 –5 < τ 0 < 10 –12 ). To further study the relaxation process of 2 , an asymmetric Cole–Cole graph based on the generalized Debye model was used to extract τ and the corresponding distribution (α) for each temperature (Figure d and Table S8). The α value was obtained in the wide range of 0.06 to 0.51, with a large relaxation time distribution, which confirmed that there might be multiple relaxation processes in 2 . , …”
Section: Resultsmentioning
confidence: 87%
“…Using the obtained parameters, we fitted both the Orbach and Raman processes (τ –1 = CT n + τ 0 –1 exp(− U eff / kT )) over the entire temperature region (10.0–30.0 K). Thus, the excellent fit to the overall relaxation was obtained, and parameters were obtained: U eff = 197.44 K (137.22 cm –1 ), τ 0 = 3.03 × 10 –7 s, C = 8.69 × 10 –5 s –1 ·K – n , n = 5.07, R 2 = 0.999, where the n value and τ 0 were consistent with normal value (1 < n < 6 and 10 –5 < τ 0 < 10 –12 ). To further study the relaxation process of 2 , an asymmetric Cole–Cole graph based on the generalized Debye model was used to extract τ and the corresponding distribution (α) for each temperature (Figure d and Table S8). The α value was obtained in the wide range of 0.06 to 0.51, with a large relaxation time distribution, which confirmed that there might be multiple relaxation processes in 2 . , …”
Section: Resultsmentioning
confidence: 87%